Penerapan Strategi Transformasi Digital Di lingkungan Manufaktur Pada Sistem Informasi Manajemen - Vera Diyah Anggriani; Rayyan Firdaus (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This journal is based on For many years, the manufacturing industry has been one of the industries that contributes to the value of the Indonesian economy, with a stable growth rate. In fact, according to a 2017 World Bank report, Indonesia was able to rank highest in ASEAN for the contribution of the manufacturing sector to the world economy with a contribution of 20.5%, The method used in this writing uses a causality quantitative research method, especially using literature materials as a source of research data or also called (Library research).the results of this study conclude that digital transformation has become a necessity for manufacturing to be able to compete in the digital era. By adopting technologies such as IoT, robotics, analytics, and cloud computing, manufacturers can improve the efficiency, productivity, and quality of their products.